Appendicular tuberculosis: a less encountered clinical entity. Issue 2 (4th February 2021) - Ambekar, Sachin; Bhatia, Mohit
Abstract : A 21-year-old female patient presented with vague lower abdominal pain associated with nausea since 2 days. On examination, she was tender in the right iliac fossa. Based on clinical presentation and radiological test finding, she was diagnosed as appendicitis and was subjected for diagnostic laparoscopy and appendectomy. Histopathology proved it to be a tubercular appendix, which is a rarely encountered entity. However, in a country like India, tuberculosis (TB) is highly prevalent; however, TB of appendix is rare and less known.